A Study on Understanding the Relationship between Predisposing and Enabling Factors on Nutritional Status among Secondary School Students (Journal of Environmental Science and Natural Resources, 2016)
Child malnutrition coexists in households and communities in Bangladesh due to illiteracy, poverty and knowledge which leading to a risk of disease and mortality. This study is a descriptive cross sectional study, which assessed nutritional status and related factors among high school children. In this study only 52.5% of respondents had a healthy weight. While 45% were underweight and 2.5% were overweight. The relationship between nutritional status and some independent variables at 5% level of significance were birth order (P=0.003), snacking habit (P=0.000), taking care of respondents (P=0.007), fathers occupation (P=0.019), mothers education (P=0.007), earning person of the family (P=0.028) and money for snacking (P=0.020). Based on results, its suggested that periodical monitoring and evaluation of nutritional status of the students should focus on underweight students. Supplementary support from school is still needed, to assist daily intake of students still underweight especially. Health and nutrition education should be taught.J. Environ. Sci. & Natural Resources, 9(1): 47-51 2016